2020
DOI: 10.22541/au.159415297.79664506
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lockdown, Social Media exposure regarding COVID-19 and the relation with self-assessment depression and anxiety. Is the medical staff different?

Abstract: Introduction. Locking the humanity in their homes, COVID-19 forced people to use the technology at hand to keep informed about the outbreak and to keep close to their loved ones. During this time, even if physical health is theoretically unaffected, keeping calm and sane can be challenging. The aim of this research was to evaluate whether exposure to COVID-19 information available in the digital space has a different impact on the mental condition of Romanian medical staff, compared to general population, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Coronavirus has become a burning issue around the world, and peoples strive in the search for relevant, correct, and updated information about COVID-19 through different digital and social media platforms (23,24) . YouTube is one of the available sources to collect the right information about COVID-19 awareness.…”
Section: Resultsmentioning
confidence: 99%
“…Coronavirus has become a burning issue around the world, and peoples strive in the search for relevant, correct, and updated information about COVID-19 through different digital and social media platforms (23,24) . YouTube is one of the available sources to collect the right information about COVID-19 awareness.…”
Section: Resultsmentioning
confidence: 99%
“…A survey on social media platforms in Romania found that nearly nine out of 10 people receive information about the pandemic through at least one social media channel every day. [7] Some academics have based their research on the fact that Twitter has proved to be an efficient and widely used social tool during the coronavirus pandemic, with many users Posting a large number of messages during the pandemic. [8] In the COV19Tweets data set, based on the study of large-scale data sets, some scholars found that the relevant content about the epidemic increased exponentially.…”
Section: The Role Of Social Media In the Pandemicmentioning
confidence: 99%